Analysis of avocado trade competitiveness between Mexico and the European Union from 2001 to 2018 - Luquez Gaitan, Carlos Ernesto Luquez; Hernández Mendoza, Natividad; Gómez Gómez, Alma Alicia (Revista Mexicana de Ciencias Agrícolas, 2022)
The avocado is a key agricultural product for Mexican exports, the association agreement between Mexico and the European Union has made it possible to enhance trade, that is why the commercial position of Mexico in the European market was determined, which was compared with the commercial position of the EU; variables such as exports, imports and production in the period 2001-2018 were taken into account, with which indices were made to determine competitiveness. The trade indices served to reveal the degree of competitiveness of both competitors; as a result, it was obtained that the avocado, even though the market share decreased, competitiveness has improved, which indicates that the demand of the European market has grown in greater quantity than Mexican exports. It is concluded, through the competitiveness indices, that trade has increased, mainly benefiting Mexican exporters, who have permanent comparative advantages, which makes them highly competitive in the production and trade of avocados.